Chinese commercial paper: The bank lending channel of monetary transmission and beyond. (10th December 2019) - Liu, Kerry
Abstract: China's commercial paper financing experienced dramatic growth in January 2019. This paper examines the bank lending channel of China's monetary transmission to commercial paper, and more broadly, the factors that affect the growth of commercial paper, which is the first of its kind in the academic literature. The main conclusions include: the bank lending channel to commercial paper exists; the performance of the real economy also has a significant effect on the growth of the commercial paper.